In vitro evaluation of different dental materials used for the treatment of extensive cervical root defects using human periodontal cells - Michel, Annemarie; Erber, Ralf; Frese, Cornelia; Gehrig, Holger; Saure, Daniel; Mente, Johannes (Clinical oral investigations, 2017)
IntroductionRepair materials for extensive cervical root defects may come in direct contact with periodontal tissues. This in vitro study compared the effects of four calcium silicate cements (CSC), one resin-modified glass ionomer cement, and one glass carbomer cement on primary human gingival fibroblasts (HGF), alveolar osteoblasts (HAO), and a human osteoblast cell line (hFOB 1.19).MethodsHGF, HAO, and hFOB were seeded on discoid test specimens. Relative numbers of viable cells were quantitatively assessed after 1 and 24 h for cytotoxicity/adhesion assays and after 4, 24, 48, and 72 h for proliferation assays. Data were statistically analyzed using non-parametric tests (α = 0.05).ResultsRelative to the control (100 %), CSC allowed for mean numbers of 71-81 % viable HGF and 80-82 % viable HAO. Then, 64 % of HGF and 56 % of HAO were assessed on GC Fuji II LC. Mean numbers of viable cells were 59-64 % HGF and 67-68 % HAO for GCP Glass Fill specimens. Cells exposed to CSC over 24 h remained viable and even increased in number. Both cell types adhered almost equally well to CSC and GC Fuji II LC. GCP Glass Fill continued to decrease cell viability and adhesion. CSC-based materials and GC Fuji II LC allowed for HGF and hFOB proliferation; however, none of the tested materials specifically stimulated cell proliferation.ConclusionsCSC characterized by low cytotoxicity. GC Fuji II LC shows moderate cytotoxic effects. ProRoot MTA, Harvard MTA, Biodentine, EndoSequence putty, and GC Fuji II LC allow HGF and HAO to adhere and HGF and hFOB to proliferate. GCP Glass Fill decreases cell viability, adhesion, and proliferation.Clinical relevanceCSC remain the paramount biologic choice for the repair of extensive cervical root defects. GC Fuji II LC might be considered in addition to CSC when the defect comprises supracrestal areas and the restoration requires superior aesthetic and mechanical characteristics.
Online: 14 May 2016
Gesehen am 30.10.2018